The Dynamics of Conflict in Public Policy Formulation: A Behavioral and Stakeholder Perspective - Shodiq, Muhammad Fajrus; Biqy, Muhammad Hakam (Fast in Social Sciences, 2025)
Conflict in public policy formulation is a complex and multidimensional phenomenon that reflects clashes of interest among stakeholders and encompasses individual behavioral dynamics, institutional positions, and the surrounding governance structures. This study aims to analyze the behavioral dimensions of conflict in the policy formulation process by integrating the behavioral conflict and stakeholder theory. A descriptive qualitative method was employed, with data collected through literature studies and policy document analysis. Data analysis was conducted through reduction, presentation, and interpretation processes. The findings reveal that conflict in public policy formulation is triggered by diverging interests and limited actor capacities, politically driven external pressures, and high cognitive heterogeneity. Six behavioral dimensions of conflict—internal, external, cognitive heterogeneity, behavioral repertoire, conflict response, and attachment dynamics—were identified as influencing the escalation and resolution of conflict within the policy context. Furthermore, power imbalances among stakeholders contribute to structural conflicts that hinder the realization of inclusive deliberative processes. The discussion highlights the strategic role of public administration in creating collaborative spaces, facilitating inter-party dialogue, and designing conflict resolution mechanisms grounded in values of participation, accountability, and transparency. Therefore, strengthening institutional capacity and designing collaborative governance structures are urgently needed to enhance public policy legitimacy and sustainability. These findings offer conceptual contributions to understanding conflict in public policy and its implications for more responsive and inclusive public administration practices.